2013
DOI: 10.1002/ps.3541
|View full text |Cite
|
Sign up to set email alerts
|

Methiozolin [5-(2,6-difluorobenzyl)oxymethyl-5-methyl-3,3(3-methylthiophen-2-yl)-1,2-isoxazoline], a new annual bluegrass (Poa annuaL.) herbicide for turfgrasses

Abstract: Methiozolin is an excellent candidate for annual bluegrass management in turfgrasses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(60 citation statements)
references
References 21 publications
2
58
0
Order By: Relevance
“…The K d values observed are consistent with other soil‐active herbicides (Table ). These data corroborate previous researchers who reported that methiozolin has soil activity for control of annual bluegrass …”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…The K d values observed are consistent with other soil‐active herbicides (Table ). These data corroborate previous researchers who reported that methiozolin has soil activity for control of annual bluegrass …”
Section: Resultssupporting
confidence: 93%
“…Overall, results indicate that ∼24% of applied methiozolin remains available for root uptake, but binds sufficiently to soil so as to resist leaching displacement. Thus, these studies indicate that methiozolin is available in soil for herbicidal activity, which has been observed in selective placement and field studies …”
Section: Resultssupporting
confidence: 63%
See 3 more Smart Citations